2020
DOI: 10.3390/genes11091109
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Alternative Splicing Defects Implicated in Myotonic Dystrophy Type I

Abstract: Myotonic dystrophy type I (DM1) is the most common form of adult muscular dystrophy, caused by expansion of a CTG triplet repeat in the 3′ untranslated region (3′UTR) of the myotonic dystrophy protein kinase (DMPK) gene. The pathological CTG repeats result in protein trapping by expanded transcripts, a decreased DMPK translation and the disruption of the chromatin structure, affecting neighboring genes expression. The muscleblind-like (MBNL) and CUG-BP and ETR-3-like factors (CELF) are two families of tissue-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 123 publications
(203 reference statements)
1
66
0
1
Order By: Relevance
“…Atypical splicing of the insulin receptor (IR) may take part in the formation of insulin resistance. The genes mentioned above represent just a few examples of the more than 30 miss regulated splicing identified in DM patient’s tissue samples or of the more than 60 aberrant splicing described in mice tissues [ 102 ].…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…Atypical splicing of the insulin receptor (IR) may take part in the formation of insulin resistance. The genes mentioned above represent just a few examples of the more than 30 miss regulated splicing identified in DM patient’s tissue samples or of the more than 60 aberrant splicing described in mice tissues [ 102 ].…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…These repeat RNAs serve as a sink for muscleblind-like (MBNL) proteins; a family of RBPs that regulate fetal to adult AS transitions critical for proper muscle, heart, and central nervous system (CNS) development 12,13 . Reduction of functional MBNL protein levels via this toxic RNA gain-of-function mechanism leads to global perturbations of AS established as causative of a number of DM disease symptoms [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…These repeat RNAs serve as a sink for muscleblind-like (MBNL) proteins; a family of RBPs that regulate fetal to adult AS transitions critical for proper muscle, heart, and central nervous system (CNS) development 12,13 . Reduction of functional MBNL protein levels via this toxic RNA gain-of-function mechanism leads to global perturbations of AS established as causative of a number of DM disease symptoms [14][15][16] .MBNL proteins have been shown to bind to YGCY cis-regulatory motifs to regulate AS outcomes of target pre-mRNAs in a positional-dependent manner whereby cassette exon inclusion is generally promoted through binding to downstream RNA motifs and repressed through use of upstream intronic elements 17 .Previous studies have indicated that MBNL-dependent AS responds to changes in MBNL concentrations across a broad, dynamic range of expression 18,19 . Using a titratable MBNL1 expression system to characterize the behavior of individual MBNL1-regulated AS events, it was previously reported that different amounts of MBNL are required to achieve half-maximal regulation with variable steepness of the dose-response curves 18 .While several studies have focused on the characterization of MBNL-dependent splicing regulation 13 , less work has been done to identify and characterize the role of other splicing factors that may coordinate with or antagonize MBNL splicing activity with the exception of CELF1 [20][21][22] .…”
mentioning
confidence: 99%
“…These foci can sequester muscleblind-like (MBNL) proteins, which subsequently lead to diminished activity and downstream deregulation of the alternative splicing of several genes [21,22]. In addition, the RNA foci cause hyper-phosphorylation and thus upregulation of the CUG-BP and ETR-3-like factors family member 1 (CELF1) via several signaling kinases [22,23]. CELF1 is also a splice factor, and its inappropriate phosphorylation results in deregulation of downstream target genes.…”
Section: Introductionmentioning
confidence: 99%